Dampak inflasi terhadap indeks sektoral di Indonesia - Glorya, Paquita (Riset Akuntansi dan Manajemen Pragmatis, 2023)
At the beginning of 2023, the inflation in Indonesia tends to increase in February and tends to decrease from March to April. Based on the phenomenon, this study aims to determine the relationship between changes in the inflation rate and returns from market indices. This study conducted observations from January 2 to April 28 2023 with a sample of indices in the capital market, namely IDXBASIC, IDXCYCLIC, IDXENERGY, IDXFINANCE, IDXHEALTH, IDXINDUST, IDXINFRA, IDXNONCYC, IDXPROPERT, IDXTECHNO, and IDXTRANS. The analysis results show that IDXINDUST, IDXNONCYC, and IDXTRANS have positive average market returns in the range from January to April 2023. At the lowest point of inflation in April 2023, except for IDXFINANCE which is zero, the average market returns from IDXHEALTH, IDXINDUST, IDXINFRA, IDXPROPERT, and IDXTRANS tend to provide positive performance. The findings of this study also imply that the inflation rate from January to April 2023 does not have a significant relationship with market returns in Indonesia.